Between-individuals and within-individual relations between self-insecurity and unpleasant repetitive thinking. Issue 8 (17th November 2022) - Huang, Alice B.; Berenbaum, Howard; McKee, Grace B.
ABSTRACT: Studies have found that self-security, defined as the acceptance of one's own weaknesses, is associated with many important outcomes. The present research examined the link between self- in security (the rejection of one's own weaknesses) and unpleasant repetitive thinking, a transdiagnostic process that appears to be a major risk factor for internalizing psychopathology. In Study 1, we examined the link at two levels: between-individuals ( N = 158 undergraduates) and within-individuals (using daily diary methods). At both levels, self-insecurity was significantly associated with repetitive thinking, even after simultaneously accounting for neuroticism/NA and self-esteem. Study 2 ( N = 280 undergraduates) replicated Study 1's findings. Additionally, Study 2 assessed repetitive thinking using reports by participants' close others: self-insecurity was significantly associated with close-others-reported repetitive thinking.